FROM KITCHEN TO COMMUNITY: DOSE-DEPENDENT PUBLIC HEALTH RISK REDUCTION OF MEAT-BORNE PATHOGENS AND SPOILAGE BACTERIA THROUGH CURRY POWDER-SALT CURING - Okon, Matthew Umanah; Igoche, Onje Kate; Adegoke, Ayodeji Anthony; Kooffreh, Kooffreh Ita; Stephen, Nsikak Umo; Nchonwu, Marycynthia Chioma (FUDMA Journal of Sciences, 2026)
Lack of refrigeration in many developing regions leads to economic and public health challenges from meat spoilage and foodborne pathogens. This research evaluates combinations of curry powder and salt as a public health intervention to reduce microbial load on beef stored at 4 ± 1 °C for 7 days. Two curing formulations were tested: a low-concentration range (0.5 - 3 g curry powder + 1 g salt/100 mL) and a high-concentration range (5 - 20 g curry powder + 5 g salt/100 mL), with untreated samples as controls. Total heterotrophic and coliform counts were measured. A significant dose-response was observed (p < 0.05): microbial loads decreased as curry concentration increased. The strongest suppression was achieved with Formulation Two (20 g curry + 5 g salt), reducing total heterotrophic bacteria count (THBC) to 3.00 ± 2 log₁₀ CFU/g and significantly suppressed coliform growth by day 7 (p < 0.05 compared to control). Thirteen bacterial species were identified, including key pathogens, and their prevalence and diversity showed an inverse relationship with curry-salt concentration. The combination of salt-induced osmotic stress and curry’s bioactive compounds effectively reduced microbial load and diversity. This study demonstrates that curry powder and salt act as preservatives and provide a scalable, culturally accepted solution for public health risk reduction. By defining concentration thresholds, this approach can help small-scale processors in low-resource settings extend meat shelf-life and reduce foodborne illness risks, particularly among vulnerable populations. Further studies are needed to assess sensory acceptance and storage stability.